Nutritional status as a predictor of mortality in elderly people with gastric cancer evaluated at a reference hospital - Cieza, Edwin (2018)
Objective: To evaluate the nutritional status as a predictor of mortality in elderly people with gastric cancer. Materials and methods: An observational, prospective and analytical study which included 47 patients over 60 years of age with a diagnosis of gastric cancer, referred to the geriatric department of the Hospital Nacional Guillermo Almenara from March 2014 to October 2015. The Body Mass Index (BMI) and the Mini Nutritional Assessment Short-Form (MNA-SF) were used to evaluate the patients. Results: Forty-seven (47) patients with a diagnosis of gastric cancer were included: 33 (70.2 %) were males, and the mean age was 75.52 (SD +/- 6.88) years for males and 77 (SD + / - 7.66) years for women. When performing the survival analysis, it was found that the nutritional assessment using the MNA-SF obtained statistical significance (p <0.05). Conclusions: In conclusion, A poor nutritional status is a prognostic factor of gastric cancer mortality in elderly people.